Down-regulation of circ-PRKCI inhibits cell migration and proliferation in Hirschsprung disease by suppressing the expression of miR-1324 target PLCB1. Issue 9 (3rd May 2018) - Zhou, Lingling; Li, Yang; Jiang, Weiwei; Zhang, Hua; Wen, Zechao; Su, Yang; Wu, Feng; Zhi, Zhengke; Shen, Qiyang; Li, Hongxing; Xu, Xiaoqun; Tang, Weibing
ABSTRACT: Circular RNAs (circRNAs) are a novel class of noncoding RNAs (ncRNAs), which have been shown to participate in intracellular RNA regulatory networks and play vital roles in many pathological processes. Recently, circular RNA_PRKCI (circ-PRKCI) has been reported to regulate cell proliferation, migration and invasion in several human cancers. Hirschsprung disease (HSCR) is a well-known congenital gut motility disorder which roots in the aberrance of cranial-caudal neural crest cell migration. In this study, we investigated whether circ-PRKCI may affect cell migration and proliferation in HSCR. Quantitative reverse transcription PCR (qRT-PCR) was performed to detect the expression of circ-PRKCI in 48 HSCR aganglionic tissues and 48 normal bowel tissues. Luciferase reporter assay and RNA immunoprecipitation (RIP) assay verified the direct interaction between miR-1324 and PLCB1 or circ-PRKCI. Cell counting Kit-8 (CCK-8) and Ethynyldeoxyuridine (EdU) assays were employed to appraise the effects of miR-1324 or circ-PRKCI on cell proliferative potential, while transwell was performed to detect the migration in vitro. We found that circ-PRKCI was significantly down-regulated in HSCR aganglionic tissues. Morever, knockdown of circ-PRKCI suppressed cell proliferation and migration in vitro. Mechanistically, we confirmed that circ-PRKCI functioned as a molecular sponge for miR-1324 to upregulate the expression of PLCB1. In conclusion, our present study revealed the important role of circ-PRKCI-miR-1324-PLCB1 regulatory network in HSCR, providing a novel insight for the pathogenesis of HSCR.